The Santa suit - Andrews, Mary Kay, 1954- (St. Martin's Press, 2021)
"From May Kay Andrews, the New York Times bestselling author of Hello, Summer, comes a novella celebrating the magic of Christmas and second chances in The Santa Suit. When newly-divorced Ivy Perkins buys an old farmhouse sight unseen, she is definitely looking for a change in her life. The Four Roses, as the farmhouse is called, is a labor of love-but Ivy didn't bargain on just how much labor. The previous family left so much furniture and so much junk, that it's a full-time job sorting through all of it. At the top of a closet, Ivy finds an old Santa suit-beautifully made and decades old. In the pocket of a suit she finds a note written in a childish hand: it's from a little girl who has one Christmas wish, and that is for her father to return home from the war. This discovery sets Ivy off on a mission. Who wrote the note? Did the man ever come home? What mysteries did the Rose family hold? Ivy's quest brings her into the community, at a time when all she wanted to do was be left alone and nurse her wounds. But the magic of Christmas makes miracles happen, and Ivy just might find more than she ever thought possible: a welcoming town, a family reunited, a mystery solved, and a second chance at love"--